Bufalin inhibits the growth and epithelial to mesenchymal transition of human gastric cancer cells via modulation of MEK/ERK pathway - Yi Zhou; Liguo Wang; Hui Lin; Yunxia Wang; Kezhu Hou (Bangladesh Pharmacological Society, 2021)
This study was designed to evaluate the anti-cancer effects of bufalin against the human gastric cancer cells and unveil the underlying mechanism. The results showed that bufalin inhibited the proliferation and colony formation of the MGC-803 gastric cancer cells and exhibited an IC50 of 10 μM. These antiproliferative effects were found to be due to the induction of G2/M cell cycle arrest. The G2/M cell cycle arrest was also concomitant with inhibition of cdc2, cdc25 and cyclin B1. Furthermore, bufalin suppressed the epithelial-to-mesenchymal transition, migration, and invasion of the MGC-803 gastric cancer cells. The Western blot analysis revealed that bufalin exerted its effects via deactivation of EK/ERK signaling pathway. Taken together, these results suggest the potential of bufalin as the lead molecule for the development of chemotherapy for gastric cancer.